FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYALAHGUNAAN NAPZA (NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF) PADA REMAJA DI WILAYAH “X” KOTA PADANG 2017 - Miswarti - (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Teenagers today are very worrying because it has been a lot of irregularities inteenagers one abuse of drugs. It is a substance which poses a particular influence to his user'senter into the body. The purpose of this research is to know the factors that are associated withthe abuse of drugs (narcotics, psychotropic drugs, and addictive substances) in the area of